Integrasi Smart Governance dan Collaborative Governance dalam Transformasi Green Port Berkelanjutan: Studi Kasus Pelabuhan Tanjung Emas Semarang - Evyana Diah Kusumawati; Karjono; Karmanis (JURNAL TRANSMA, 2026)
Climate change has become a significant global challenge affecting the maritime and port sectors, with rising sea levels and land subsidence threatening port operations in coastal areas. As a critical logistics hub in Indonesia, Tanjung Emas Port faces complex environmental pressures including tidal flooding, land subsidence reaching 6.51 cm per year, and carbon emissions from port activities. This study analyzes how the integration of smart governance and collaborative governance supports sustainable Green Port transformation at Tanjung Emas Port, Semarang. The research employs a qualitative case study approach with data collection through documentation studies of Pelindo reports, government policy documents, academic publications, and relevant secondary sources. Thematic analysis is used to examine three main aspects: Green Port implementation, smart governance practices, and collaborative governance practices. Findings reveal that Green Port transformation is manifested through renewable energy adoption, digitalization of port services, integrated waste management, and climate adaptation infrastructure. Smart governance enables real-time data integration and evidence-based decision-making through systems such as integrated control rooms, OCR technology, and online truck booking systems. Collaborative governance operates through a pentahelix model involving local government, port operators, businesses, communities, and academics. The study contributes a Smart Collaborative Green Port Governance (SCGPG) model as a conceptual framework for sustainable port development. This research concludes that Green Port success depends not only on green technology investment but also on governance capacity that integrates data systems and strengthens multi-stakeholder collaboration.